Ferroan olivine‐bearing eucrite clasts found in howardites. (4th March 2018) - Patzer, Andrea; McSween, Harry Y.
Abstract: We investigated several olivine‐bearing, medium‐grained, ophitic to subophitic eucritic clasts from three different Antarctic howardites. Based on grain size (0.5–2 mm), these clasts could represent intrusive igneous units. Based on mineral composition (pyroxene and plagioclase), they are similar to basaltic eucrites. Elemental concentrations of the major silicates and bulk mg#, however, range from those known for basaltic eucrites to those found in cumulate eucrites. Recognizable cumulus phases are absent. Conservatively speaking, the clasts examined may simply classify as relatively coarse‐grained unequilibrated basaltic eucrites. Alternatively, at least one of the clasts showing intermediate grain size and a relatively primitive chemical composition (mg# 50) may sample a rock type that could be genetically placed between the basaltic and cumulate eucrite lines of origin. A minor, yet genetically meaningful common feature of the clasts studied is the occurrence of fayalitic olivine. Two distinct categories exist. They are (1) fine veinlets exclusively percolating through pyroxene and (2) more substantial (up to 100 μm wide) veins and/or interstitial deposits. Only the fine veinlets also contain variable amounts of anorthite, ilmenite, and troilite. Although both types of olivine are ferroan, textural aspects suggest distinct paths of generation. The fine veinlets are best explained by decomposition of relatively FeO‐rich, heterogeneous, and locally metastable pyroxene, caused in situ by impact heating and subsequent fast cooling. The wider, often very ragged‐looking monomineralic olivine fillings, on the other hand, may represent the iron‐enriched portion of a highly fractionated magma.